Evaluation of Psychological Distress in Infertile Women who Underwent ART Cycle During the COVID-19 Pandemic - Cogendez, Ebru; Kumru, Pinar; Soysal, Sunullah; Ozkaya, Enis; Devranoglu, Belgin; Tozkir, Elif; Sanverdi, Ilhan (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: We aimed to determine the frequency of psychological distress and related factors in infertile women who underwent assisted reproductive technologies during the COVID-19 pandemic and to develop health policies accordingly. STUDY DESIGN: This cross-sectional study was carried out with 352 infertile women who applied to the in vitro fertilization clinic between December 2020-February 2021. In the face-to-face survey study, five questionnaires were given to all participants: (1) a Questionnaire regarding the socio-demographic/general health characteristics of the patient, (2) Impact of Event Scale-Revised, (3) Beck’s Depression Inventory, (4) State-Trait Anxiety Inventory -1, (5) State-Trait Anxiety Inventory-2. RESULTS: Post-traumatic stress disorder was detected in 129 (36.6%) infertile women. In cases of diminished ovarian reserve and oocyte freezing; a significantly higher incidence of post-traumatic stress disorder was found compared to patients with unexplained infertility, polycystic ovary syndrome, and male factor infertility (p=0.004). Minimal-mild depression level was detected in 295 (83.8%) participants, and moderate-severe depression level was found in 57 (16.2%) participants. The mean State-Trait Anxiety Inventory-1 and State-Trait Anxiety Inventory-2 scores of infertile women were 43.5±6.7 and 46.6±6.3, respectively. A statistically significant relationship was found between the duration of infertility and moderate-severe anxiety according to State-Trait Anxiety Inventory-1 (p=0.046). CONCLUSION: Our findings show that women with long-term infertility and undergoing oocyte freezing are the most affected patients by the pandemic. It would be appropriate for in vitro fertilization centers to provide psychological support to patients that have a mentally high risk of distress.